2018
DOI: 10.1177/2394901518795067
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Government Expenditure on Private Investment in Nigerian Economy (1980–2016)

Abstract: This study examined the effect of government expenditure on private investment in Nigeria during the period 1980–2016. The error correction model analysis was used in the study to analyze the relationship between the two variables. The study found that there is a long-run relationship among the variables and that the interest rate and inflation have negative but significant impact on private investment in the long run. On the other hand, government expenditure has positive but insignificant impact on private i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 22 publications
3
8
0
Order By: Relevance
“…Also, moderate rise in inflation might boost the marginal propensity to profit for domestic investor, being incentive to investment even when the cost of production rises, provided that elasticity demand for those product are fairly inelastic. These results lends credence to earlier studies, such as Petrović et al (2020), Deleidi et al (2020), Deleidi (2018), Berperogiou et al (2017, Magableh and Ajlouni (2016) and Olayungbo and Olayeni (2018), Ouedraogo et al (2019), Maingi (20017), Akinlo et al (2018), Bahal et al (2018), Miyamoto et al (2017) and Ambler et al (2017). While it contradicts the ealier findings of Funashima et al (2019), Furceri et al (2018) and Nguyen and Trinh (2018).…”
Section: Ardl Estimatessupporting
confidence: 83%
“…Also, moderate rise in inflation might boost the marginal propensity to profit for domestic investor, being incentive to investment even when the cost of production rises, provided that elasticity demand for those product are fairly inelastic. These results lends credence to earlier studies, such as Petrović et al (2020), Deleidi et al (2020), Deleidi (2018), Berperogiou et al (2017, Magableh and Ajlouni (2016) and Olayungbo and Olayeni (2018), Ouedraogo et al (2019), Maingi (20017), Akinlo et al (2018), Bahal et al (2018), Miyamoto et al (2017) and Ambler et al (2017). While it contradicts the ealier findings of Funashima et al (2019), Furceri et al (2018) and Nguyen and Trinh (2018).…”
Section: Ardl Estimatessupporting
confidence: 83%
“…This finding contrasts the results of Afonso and Aubyn (2019), Yovo (2017) and Dash (2016). However, it corroborated Nguyen and Phong (2018), Akinlo and Oyeleke (2018) and Xu and Yan (2014). Foye (2014) employed Ordinary Least Square Model to probe the relationship between public capital spending and private investment in Nigeria from 1970 to 2006.…”
Section: Government Capital Expenditure and Private Sector Investmentmentioning
confidence: 86%
“…In the same vein, they submitted that public investment is positively related to domestic private investment and foreign direct investment both in the short-and long-run. Moreover, Akinlo and Oyeleke (2018) used error correction model to analyze the relationship between government expenditure and private investment in Nigeria over the period 1980 to 2016. Their findings indicated that inflation and interest rate have a significant adverse effect on private sector investment in the long run, while government expenditure is positively related to private investment.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations